Alienation as a Predictor of Career Anxiety: An Empirical Study of Generation Z in Bengkulu Indonesia - Lola Amellia; Panji Suminar; Ika Pasca Himawati3 (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Although Generation Z is widely regarded as adaptive in the digital era, this cohort also faces significant social and economic pressures in career planning. However, empirical evidence on the influence of social alienation on career anxiety in non-Western contexts, particularly in Indonesia, remains limited. Therefore, this study aims to examine the effect of alienation on career anxiety among Generation Z in Bengkulu City, drawing on Émile Durkheim’s theory of anomie, which posits that the weakening of social norms may lead to alienation and uncertainty about life direction. This study employed a quantitative approach using a cross-sectional survey design. The sample consisted of 380 Generation Z respondents aged 20–24 years, selected through purposive sampling. Data were collected using structured questionnaires that measured alienation based on Seeman’s (1959) conceptual framework with local adaptation, as well as career anxiety, and were analyzed using simple linear regression in SPSS. All instruments met the criteria for validity (r > 0.1005) and reliability (Cronbach’s Alpha > 0.60). The results indicate that alienation significantly predicts career anxiety (β = 0.64, p < .001), with the regression equation Y = 27.489 + 0.757X. Alienation accounts for 41% of the variance in career anxiety (R² = .41), indicating a moderate to strong effect size. These findings confirm the relevance of Durkheim’s theory of anomie in understanding the contemporary social dynamics of Generation Z in Indonesia. In practice, the results highlight the importance of developing career guidance and counseling programs that integrate psychosocial dimensions, particularly reducing social alienation, to mitigate career anxiety among Generation Z. Keywords: alienation, generation Z, bengkulu city, career anxiety